Specialist group therapy for psychological factors associated with firesetting: Evidence of a treatment effect from a non-randomized trial with male prisoners. (October 2015) - Gannon, Theresa A.; Alleyne, Emma; Butler, Helen; Danby, Harriet; Kapoor, Aparna; Lovell, Tamsin; Mozova, Katarina; Spruin, Elizabeth; Tostevin, Tracey; Tyler, Nichola; Ó Ciardha, Caoilte
Abstract: Despite huge societal costs associated with firesetting, no standardized therapy has been developed to address this hugely damaging behavior. This study reports the evaluation of the first standardized CBT group designed specifically to target deliberate firesetting in male prisoners (the Firesetting Intervention Programme for Prisoners; FIPP). Fifty-four male prisoners who had set a deliberate fire were referred for FIPP treatment by their prison establishment and psychologically assessed at baseline, immediately post treatment, and three-months post treatment. Prisoners who were treatment eligible yet resided at prison establishments not identified for FIPP treatment were recruited as Treatment as Usual controls and tested at equivalent time-points. Results showed that FIPP participants improved on one of three primary outcomes (i.e., problematic fire interest and associations with fire), and made some improvement on secondary outcomes (i.e., attitudes towards violence and antisocial attitudes) post treatment relative to controls. Most notable gains were made on the primary outcome of fire interest and associations with fire and individuals who gained in this area tended to self-report more serious firesetting behavior. FIPP participants maintained all key improvements at three-month follow up. These outcomes suggest that specialist CBT should be targeted at those holding the most serious firesetting history. Highlights: We examine a new CBT group therapy designed to target deliberate firesetting. Therapy improved problematic fire factors and violent/antisocial attitudes. All post treatment improvements were stable at three-month follow up.